KETEPATAN PENGODEAN DIAGNOSIS TURBERKULOSIS DI RSUD KOTA TANGERANG - Lusiana Darmawan; Nauri Anggita Temesvari; Hosizah Hosizah (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2024)
Abstract: Disease coding is one of the important things in providing health information. Coding is used to code diseases according to WHO regulations regarding diagnosis codes consisting of letters and numbers, thereby facilitating the disease reporting process. Coding relies heavily on the clarity of the diagnosis written by the doctor to provide quality information. Inaccuracy of the codes given during the coding process will affect the hospital's reporting activities and decision making. The aim of this research is to determine the relationship between the clarity of writing a diagnosis and the accuracy of coding a diagnosis of tuberculosis at the Tangerang City Regional Hospital. This type of research is quantitative research using a cross sectional research design. The sample consisted of 72 inpatient medical records of tuberculosis patients using a purposive sampling technique. Data analysis was carried out using univariate analysis and bivariate analysis with the Chi-Square test. The results of the study showed that the clarity of writing a clear diagnosis was 49 (68.1%) and the writing of a tuberculosis diagnosis was unclear in 23 (31.9%) of the inpatient medical records of tuberculosis patients. Meanwhile, the accuracy of coding a diagnosis of tuberculosis was 38 (52.8%), and the accuracy of coding an incorrect diagnosis was 34 (47.2%) from 72 medical records. The p-Value = 0.000 (0.000<0.05) so that there is a significant relationship between the clarity of writing a diagnosis and the accuracy of coding a diagnosis of tuberculosis.Â Keywords: Clarity, Coding Accuracy, Tuberculosis Abstrak: Pengodean penyakit merupakan satu diantara hal penting dalam penyediaan informasi kesehatan. Pengodean digunakan untuk memberi kode penyakit sesuai aturan WHO tentang kode diagnosis yang terdiri dari huruf angka sehingga memudahkan proses pelaporan penyakit. Pengodean sangat bergantung pada kejelasan penulisan diagnosis yang ditulis dokter guna menyediakan informasi yang berkualiktas. Ketidaktepatan kode yang diberikan pada proses pengodean akan berpengaruh terhadap legiatan pembuatan pelaporan dan pengambilan keputusan rumah sakit. Tujuan penelitian ini adalah untuk mengetahui hubungan kejelasan penulisan diagnosis dengan ketepatan pengodean diagnosis penyakit tuberkulosis di RSUD Kota Tangerang. Jenis penelitian ini adalah penelitian kuantitatif dengan menggunakan desain penelitian Cross Sectional. Sampel terdiri dari 72 rekam medis rawat inap pasien tuberkulosis dengan teknik pengambilan secara purposive sampling. Analisis data dilakukan dengan analisis univariat dan analisis bivariat dengan uji Chi-Square. Hasil penelitian menunjukkan bahwa kejelasan penulisan diagnosis yang jelas sebanyak 49 (68,1%) dan penulisan diagnosis tuberkulosis yang tidak jelas sebanyak 23 (31,9%) rekam medis rawat inap pasien tuberkulosis. Sedangkan ketepatan pengodean diagnosis penyakit tuberkulosis sebanyak 38 (52,8%), dan ketepatan pengodean diagnosis yang tidak tepat sebanyak 34 (47,2%) dari 72 rekam medis. Nilai p-Value = 0,000 (0,000<0,05) sehingga ada hubungan bermaksa antara kejelasan penulisan diagnosis dengan ketepatan pengodean diagnosis penyakit tuberkulosis.Â Kata kunci: Kejelasan, Ketepatan Pengodean, TuberkulosisÂ